Exploring social worker's experiences working with child sexual abuse survivors who are intellectually disabled. - Samuels, Leandre (Department of Social Development, 2026)
Sexual abuse of children with intellectual disabilities is a global phenomenon. The study aimed to explore social workers' experiences working with child sexual abuse survivors with intellectual disabilities. The study employed a qualitative research design, specifically a qualitative descriptive and explorative design. The study design reflects a commitment to upholding the rights, safety, and well-being of both the social workers involved and the vulnerable populations they serve. Given the sensitive and emotionally charged nature of this study, strict ethical guidelines were followed to ensure the protection and dignity of all participants. Ethical approval was obtained from the UCT Ethics review committee, and all participants provided informed consent before participation. The study prioritized confidentiality, anonymity, and voluntary participation, allowing participants to withdraw at any stage without consequence. Semi-structured face-to-face interviews were held with 14 participants across the Cape Metro who have more than 5 years of experience within the field of child sexual abuse. Through purposive and snowball sampling techniques, the sample consisted of 14 participants, 13 female and one male. The study employed a thematic analysis using Braun and Clarke's thematic analysis. The findings of the study revealed the unique challenges social workers experience with child sexual abuse survivors' intellectual disabilities. The challenges included vicarious trauma, communication difficulties, lack of available resources, and ethical and legal dilemmas, including seeking justice. Furthermore, participants often face systemic barriers such as inadequate training and a lack of intervention strategies. Practice models utilized by participants are adapted from international guidelines. Thus, participants must adapt the guidelines based on the intellectual level of the child survivor. Moreover, the current legislation and policies available are silent when addressing the needs of the child sexual abuse survivor with intellectual disabilities. The study underscores the need for alternative communication methods, tailored intervention approaches, specifically for South Africa, and comprehensive training programmes to empower social workers in the field of intellectually disabled child sexual abuse. Furthermore, the findings highlighted the need for stakeholder collaboration and policymakers to include and implement policies relating to child sexual abuse survivors with intellectual disabilities.